THE KOMBINASI INTERVENSI MILL’S MANIPULATION DAN ULTRASOUND SAMA BAIK DENGAN KOMBINASI TRANSVERSE FRICTION DAN ULTRASOUND TERHADAP PENURUNAN NYERI PADA TENNIS ELBOW TIPE II - Gautama, Dwi Halim Kevin; Winaya, I made Niko; Muliarta, I Made (Majalah Ilmiah Fisioterapi Indonesia, 2015)
Daily activities that involve excessive work of the upper extremity can cause problems to the lateral humeral epycondylus known as tennis elbow. The purpose of this research was to compare the combination of mill’s manipulation and ultrasound with combination of transverse friction and ultrasound to reduce pain in tennis elbow type II. This research used an experimental research with Pre and Post Test Two Group Design. Samples were divided into two treatment groups, which are mill’s manipulation and ultrasound group that consists of 10 samples and transverse friction and ultrasound group that consists of 10 samples. The measured data is VAS (Visual Analogue Scale) before and after the intervention. The result of this research is, Group 1 occurring on average decrease with p=0.000 (p>0.05), while on Group 2 occurring on average decrease with p=0.000 (p>0.05), once compared Group 1 and Group 2 p=0.697 (p>0.05), meaning that there was no significant difference in the decrease in VAS score between the two groups. From this research it can be concluded that the combination of mill’s manipulation and ultrasound showed no significant result as combination of transverse friction and ultrasound to reduce pain in tennis elbow type II.
Keywords: Tennis elbow type II, pain, mill’s manipulation, transverse friction and ultrasound